The Pictorial Interview of Children's Metacognition and Executive Functions (PIC-ME): Cultural Adaptation for Ultra-Orthodox Jewish Populations - Anat Golos; Jennifer R. Budman; Ayala Shterenshus; Ruthie Traub Bar-Ilan (Hindawi-Wiley, 2023)
Introduction. Executive functions (EFs) are strongly linked to attention deficit hyperactivity disorder (ADHD). The pictorial interview of children's metacognition and executive functions (PIC-ME) assesses children's self-perceptions regarding their EF. This study is aimed at describing the cultural adaptation of the PIC-ME to the ultra-Orthodox (UO) Jewish population in Israel. Method. In the first of three stages, 30 occupational therapists, who were experienced in working with children with ADHD from the UO population, completed a questionnaire about the suitability of PIC-ME for the UO community. In the second stage, six therapists participated in a focus group to discuss the recommendations and the adaptations made following the first stage. In the third stage, 20 UO children aged 5-10 participated in the tool validation process. Results. First stage: most of the items of the original tool were found to be appropriate in representing the EFs of UO children and did not need to be adapted. No significant differences were found between the boys' and girls' versions regarding the tool's adaptability. However, most of the therapists suggested that the pictures in both versions needed adaptations. Second stage: additional recommendations led to the development of a final adapted version. Third stage: over 70 percent agreement was found among UO children regarding the clarity of the adapted pictures. No significant differences were found between boys and girls or between age groups. Conclusions. This study presented wide agreement on the necessity for cultural adaptation of the PIC-ME to the UO population and described the adaptation process. Based on its face validity, the UO version may be a useful tool to assess the self-perception of EF among UO children. Further studies are needed to assess its psychometric properties and its usefulness as an outcome measure. The study findings may contribute to the cultural adaptation of other tools for culturally distinct populations.